2019
DOI: 10.18502/ijaai.v18i3.1119
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Serum Levels of Cytokines in Schizophrenic Patients before and after Treatment with Risperidone

Abstract: A growing body of evidence suggests the existence of abnormalities in the immune system of schizophrenic patients. The current study examined serum levels of interleukin (IL) -1β, IL-6, IL-2,interferon(IFN) -γ, and tumor necrosis factor(TNF)-α in schizophrenic patients before and after treatment with risperidone and correlated levels of these cytokines with symptomatology. The study group consisted of 24 schizophrenic patients as defined by Diagnostic and Statistical Manual of Mental Disorders 4th editio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Heterogeneity among studies was marked (I 2 = 74%). After exclusion of the two main heterogeneity contributing studies (Azizi et al [ 38 ]; Subbanna et al [ 35 ]) the results provided the same conclusion. At baseline measurements, levels of IL-1β were significantly higher ( p = 0.02) than HC, but after treatment, this elevation became statistically insignificant ( p = 0.13).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Heterogeneity among studies was marked (I 2 = 74%). After exclusion of the two main heterogeneity contributing studies (Azizi et al [ 38 ]; Subbanna et al [ 35 ]) the results provided the same conclusion. At baseline measurements, levels of IL-1β were significantly higher ( p = 0.02) than HC, but after treatment, this elevation became statistically insignificant ( p = 0.13).…”
Section: Resultssupporting
confidence: 52%
“…At baseline measurements, the levels of TNF-α were significantly higher ( p = 0.0002) than HC, but after treatment, this elevation became statistically insignificant ( p = 0.09). Individual exclusion of Azizi et al [ 38 ], Juncal-Ruiz et al [ 32 ], Noto et al [ 40 ] studies rendered the results insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has been proposed that immunologic abnormalities are likely to be involved in the development of schizophrenia ( 37 ), and several previous studies did find the upregulation of proinflammatory cytokine levels and downregulation of anti-inflammatory cytokine levels in first-episode and drug-naïve schizophrenia patients ( 38 , 39 ), while some other studies failed to replicate the results and even presented the opposite direction ( 40 , 41 ). A recent study found that antipsychotic drugs could modulate inflammation levels and alleviate clinical symptoms in schizophrenia ( 42 ), but also with mixed results between other studies ( 43 ). The discrepancies in studies may be attributed to several factors, including different sample sizes, antipsychotic drugs used, duration of treatment, and different disease statuses.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of inflammatory cytokines have also been observed in patients with schizophrenia. Studies regarding humans and animals have identified chronic inflammation as a risk factor for schizophrenia [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%